Kadar C-Reactive Protein dan Laju Filtrasi Glomerulus Pasien Diabetes Melitus Tipe 2 Obesitas di RSUD Margono Soekarjo Purwokerto - Pugud Samodro; Hernayanti Hernayanti; Gesa Gestana A; Agus Prastowo (Poltekkes Kemenkes Yogyakarta, 2016)
Background. C-Reactive Protein, which is an acute protein as an inflammation marker, is elevated in Type 2 Diabetes Mellitus (T2DM) with obesity. One of the complications of T2DM is diabetic nephropathy, which the kidney disorder occurs due to the atherosclerosis that would cause renal vasoconstriction and decreased Glomerula Filtration Rate (GFR). Objectives. To analyze the correlation of CRP level with GFR in patients with T2DM and obesity in RSUD Margono Soekarjo Purwokerto. Methods. The design of this study is observational analytic with cross sectional approach, carried out on 48 patients T2DM with obesity in Internal Clinic RSUD Margono Soekarjo, aged 35-60 years old. Subjects who use Insulin therapy, antibiotics, anti-inflammatory and diuretic medications, which suffer from kidney disease, liver disease, infection , trauma and dehydration were excluded from the study. Data were analyzed with the Pearson correlation test. Where p < 0,05 indicates a significant correlation. CRP levels were tested with hs-CRP test and GFR calculate with the MDRD formula. Results. Results of the analysis with the Pearson correlation test between CRP levels and GFR values obtained p = 0,045 and r = -0,290. There is a significant correlation between CRP levels and GFR, with negative and moderate correlational strength. Conclusion. There is a correlation between CRP levels and GFR in patients with Type 2 Diabetes and obesity in RSUD Margono Soekarjo Purwokerto. Keywords : C-Reactive Protein (CRP), high sensitivity C-Reactive Protein (hsCRP), Glomerular Filtration Rate (GFR), Type 2 Diabetes with Obesity.